Dementia buddying as a vehicle for person-centred care? The performance of a volunteer-led pilot on two hospital wards. Issue 3 (July 2018) - Preston, Claire; Burch, Sarah
Objectives: To understand and explain whether a dementia buddies pilot introduced into two adjacent mental health hospital wards in England was achieving its aim of enhancing person-centred care. Methods: The research used a cultural lens to evaluate the dementia buddies pilot. It comprised 20 in-depth semi-structured interviews with staff, volunteers and carers in the two wards where the pilot was introduced. Results: The pilot's ability to deliver positive outcomes depended on its compatibility with the culture of the ward and it performed better in the ward where a person-centred culture of care already existed. In this ward, the pilot became a catalyst for improved experience among patients, carers and staff, whereas in the second ward, the pilot faced resistance from staff and achieved less. Conclusions: This finding underlines the benefit of focusing on workplace culture to understand the performance of volunteer-led initiatives. It also shows that existing ward culture is a determining factor in the capacity for dementia buddy schemes to act as vehicles for culture change.